Children and cutaneous leishmaniasis: a clinical report and review - Pouran Layegh; Toktam Moghiman; Seyed Amir Ahmadian Hoseini (Journal of Infection in Developing Countries)
Introduction: Mashhad, located in north-east Iran, is one of the most important regions for cutaneous leishmaniasis (CL) due to Leishmania tropica. Children account for 7-10% of the infected population in the endemic areas. Despite the high sensitivity and susceptibility of this age group, no comprehensive study has yet investigated the clinical characteristics and demographic data in children in our region. Therefore, we aimed to study the clinical features and demographic information in children visiting the Leishmania clinic of two main teaching hospitals.